Bridging Fusha and ‘Ammiyah: Rethinking Arabic as a Foreign Language Curriculum in Diglossic Contexts - Nursyahidatul Urwati; Zailani Novian; Abd Syakur; Sarah Salsabila; Hesti Agustin (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Although Arabic diglossia between fusha and ‘ammiyah has been widely examined in sociolinguistic studies, Arabic as a Foreign Language curricula in Indonesia largely remain fusha-centered and structurally oriented, with limited attention to the sociolinguistic and communicative realities of Arabic-speaking communities. This study addresses this gap by examining the functional use of fusha and ‘ammiyah in social interaction and analyzing their implications for Arabic language curriculum development in Indonesia. Employing a descriptive qualitative approach based on a critical review of relevant sociolinguistic and pedagogical literature, this research synthesizes conceptual findings on Arabic diglossia and curriculum orientation. The findings indicate that the dominance of a fusha-centered structural approach creates a mismatch between learners’ linguistic competence and the communicative practices of native Arabic speakers, who predominantly rely on ‘ammiyah in everyday interaction. This study contributes to Arabic language pedagogy by proposing a conceptual framework for integrating selective ‘ammiyah elements into the curriculum alongside the development of intercultural communicative competence. Such integration is expected to enhance learners’ contextual, pragmatic, and sociocultural abilities, enabling more effective and authentic communication in real-life Arabic-speaking environments.